The determinants of risk reporting during the period of adoption of Basel II Accord: Evidence from the Portuguese commercial banks - Azevedo, G.; Oliveira, J.; Sousa, L. M. C.; Borges, F. (Asian Review of Accounting, 2022)
The purpose of this paper to analyze the risk reporting practices and its determinants of commercial banks during the period of the adoption of the Basel II Accord in Portugal. The paper conducts a content analysis of the risk and risk management sections included in the management reports and the notes of the annual reports of Portuguese commercial banks, for the years 2007, 2010 and 2013. Findings show that theoretical frameworks underpinned in agency and legitimacy theories continue to provide valid explanations for risk reporting by Portuguese banks. More specifically, findings indicate that agency costs, public visibility and reputation are crucial drivers of risk reporting. Findings also indicate that younger banks with lower risk management skills use risk reporting either as an informational process or as a channel to manage organizational legitimacy. The content analysis does not allow readily for in-depth qualitative inquiry. The coding instrument is subject to coder bias. Information about risk can be provided in sources other than annual reports. Additionally, not all banks disclose information on corporate governance-related variables that could also influence risk reporting. The current research setting has never been studied hitherto. In this sense, this study seems to be of great relevance given the scarcity of literature on the subject in Portugal.